Taxonomy of the leafhopper genus Distantasca (Hemiptera: Cicadellidae: Typhlocybinae: Empoascini) with description of a new species from Australia - Wang, Ran; Selleck, Cait; Zhang, Yalin; Cao, Yanghui (Zootaxa, 2025)
A new species Distantasca parasmithi Wang & Cao sp. nov. is described from Australia, and is also recorded from Papua New Guinea. Illustrations of the male genitalia, habitus photos and host information of the new species are provided. The generic characteristics are redefined. A key to males of all known species of Distantasca is also given.